Correlation Of Serum Cardiac Troponin I With Significant Left Ventricular Systolic Dysfunction In Patients With Chronic Heart Failure (KYAMC Journal, 2017)
Objective: The aim of the study was to observe the relationship between elevated levels of serum cardiac Troponin I (cTnI) and in-hospital morbidity & mortality in chronic heart failure with LV systolic dysfunction.Background: Chronic heart failure is a public health problem in the United Kingdom and also in our country. Serum Cardiac troponin I (cTnI) has been validated as a sensitive and specific marker of cardiac myocyte damage and is elevated in some patients with chronic heart failure with LV systolic dysfunction and predicts adverse outcome.Materials and Methods: This study was prospective, cross sectional and observational study. The study was carried out among chronic heart failure with LV systolic dysfunction patients in the Department of Cardiology, National Institute of Cardiovascular Diseases, Sher-E-Bangla Nagar, Dhaka, during the period of April 2004 to December 2004. In this Study, total 740 patients of heart failure were evaluated Among 740 patients, initially 100 patients were selected as chronic heart failure on the basis of inclusion & exclusion criteria, history, physical examination, biochemical, X-ray, ECG & other relevant investigations. Finally, 60 patients were selected by echocardiography who had ejection fraction of 40%. Cardiac troponin I was measured in each and every studied patient. In-hospital outcome was observed in terms of morbidity & mortality. So hospitalised patients were followed up clinically and by investigation. Results: The results of this study revealed that serum cTnI was significantly elevated (cTnI 0.04 ng/ml) in serum of 29 patients (48.33%) and low or insignificant (cTnI 0.04 ng/ml) in serum of 31 patients (51.67%). Patients with significantly elevated serum cardiac troponin I (cTnI) level (group-A) had significantly higher inhospital morbidity & mortality than patients who had insignificant serum cardiac troponin I (cTnI) level (group-B). In-hospital mortality was 15% (number of death 09) out of total 60 patients. All expired patients were in NYHA class-IV. On the other hand, there was no mortality in group-B. In-hospital morbidity was 2.75 times higher among the patients who had significantly elevated serum cTnI level. A significant correlation was found between the patients who had significantly elevated serum cTnI level (cTnI level > 0.04 ng/ml) and the patients who had insignificant serum cTnI level (cTnI level < 0.04 ng/ml) in consideration to in-hospital morbidity & mortality.Conclusion: Conclusion of this study is that serum cardiac troponin I (cTnI) level is significant predictor of increased morbidity & mortality in chronic heart failure. with LV systolic dysfunction. Serum Cardiac troponin I (cTnI) level may be a useful tool for identification, selection of therapeutic strategies and assessment of prognosis in patients with chronic heart failure who are at increased risk of ventricular systolic dysfunction and death. So it is a message for the physician as well as patients.KYAMC Journal Vol. 5, No.-2, Jan 2015, Page 503-508